THE EVALUATION OF ENHANCING CHARACTER EDUCATION PROGRAM: Empirical Study using the Context, Input, Process, and Product (CIPP) Method at Buddhist Colleges in Banten - Suparmanto; Prof. Dr. Billy Tunas; Dr. Widodo Sunaryo (JF Publisher, 2023)
This research aims to find efforts and strategies to improve the character education strengthening program by producing recommendations for the continuation of the next character education strengthening program. This research uses the Context, Input, Process, and Product (CIPP) method with the samples in this research are Lecturers, Rector/Director of Higher Education and Higher Education Officials of the Ministry of Education and Culture related to the Character Education Strengthening Program at Buddhist Universities in Banten. The results of character education strengthening program at the Buddhist Colleges in Banten takes the form of outputs and outcomes in order to form graduates of Buddhist Colleges with national character. Based on the results of the CIPP analysis, in the Context component, the character education strengthening program at Buddhist Colleges in Banten includes aspects of requirements analysis, the objectives, targets and policies getting